Conceptual database design for smart medical clinical system - Mohd Sani, Nor Fazlida; Affendey, Lilly Suriani; O. K. Rahmat, Rahmita Wirza; Selamat, Mohd Hasan; Abdul Kadir, Rabiah; Dimon, Mohd Zamrin (IEEE, 2012)
Hospitals are known for having separate information systems across various departments, which are usually heterogeneous in nature. Medical experts could benefit greatly from the integration of these islands, but the heterogeneity of the sources/databases often impedes this. Most cardiothoracic units use isolated heterogeneous systems to keep patients records as well as to support the experts when deciding for cardiothoracic surgery. These include patient’s information system, lab results for x-ray, angiography, echocardiogram, blood etc. All these information are stored in heterogeneous systems and as such, a user would have to log-in and log-out from one system to another, to monitor/trace a patient’s medical record. As the solution, we proposed a clinical database system in which the system incorporates the overall patient’s management, from ward admission through Operation Theatre, Coronary Intensive Care Unit (CICU), recovery and discharge in which is divided into several modules. The purpose of this paper is to presents the conceptual database design for the Smart Medical Clinical System which include features that could alert the healthcare personnel regarding any abnormal trend in the data, so that medical experts need not have to repeat the same investigations.